THE DEVELOPMENT OF “KOMLABIL” (KOMIK POLA BILANGAN) MEDIA IN LEARNING NUMERICAL PATTERNS - Machmud, Tedy; Hulopi, Renata; Damayanti, Taulia (Universitas Bhinneka PGRI, 2025)
In the era of globalization, marked by the rapid development of technology, various innovations continue to emerge, including in the education sector. The application of digital transformation in education involves the use of information and communication technology to impact the improvement of learning quality, expand access to learning resources, and create a more interactive and collaborative learning environment. Thus, the education sector has become one of the most responsive fields to technological advancements. This study developed a learning media in the form of comics, named